Pengenalan dan Pelatihan Fish Finder kepada Masyarakat Nelayan di Desa Sungsang IV Kabupaten Banyuasin Sumatera Selatan - Beta Susanto Barus; Riris Aryawati; Muhammad Hendri; Andi Agussalim; Gusti Diansyah; Sefti Heza Dwinanti (Universitas Pahlawan Tuanku Tambusai, 2022)
Sungsang IV Village is a village where most of the residents work as fishermen. The waters around this village have great fishery potential. The results of fish catches by fishermen are felt to be less than optimal due to a lack of knowledge about the latest technology in fishing. Fish Finder is one alternative that can be given to solve this problem because this tool can function to detect the presence of fish. Most of the residents of Sungsang IV Village don't know about the Fish Finder tool. This service activity aims to provide introduction and training regarding the use of Fish Finder to detect the presence of fish. The enthusiasm of the community is very visible from the number of training participants that exceeds the targeted number. This training is carried out by presenting material and direct practice of using the tool to make it easier for participants to understand the operating steps. The results of the evaluation of the questionnaire conducted showed that all participants felt very helpful with the training in the use of this Fish Finder tool.